Development and validation of the first point-of-care assay to objectively monitor adherence to HIV treatment and prevention in real-time in routine settings. (1st February 2020) - Gandhi, Monica; Wang, Guohong; King, Roger; Rodrigues, Warren C.; Vincent, Michael; Glidden, David V.; Cressey, Tim R.; Bacchetti, Peter; Spinelli, Matthew A.; Okochi, Hideaki; Siriprakaisil, Oraphan; Klinbuayaem, Virat; et al.
Abstract : Objective: HIV prevention and treatment studies demonstrate that pharmacologic adherence metrics are more accurate than self-report. Currently available metrics use liquid-chromatography/tandem-mass-spectrometry (LC-MS/MS), which is expensive and laboratory-based. We developed a specific and sensitive antibody against tenofovir, the backbone of treatment and prevention, but conversion to a lateral flow assay (LFA) – analogous to a urine pregnancy test – is required for point-of-care testing. We describe the development of the first LFA to measure antiretroviral adherence in real-time. Methods: Previous work in a directly observed therapy study of providing tenofovir disoproxil fumarate (TDF) to HIV-noninfected volunteers at various simulated adherence patterns defined the appropriate cut-off for the LFA (1500 ng tenofovir/ml urine). We developed the LFA using a sample pad for urine; a conjugate pad coated with TFV-specific antibodies conjugated to colloidal gold nanoparticles; a nitrocellulose membrane striped with tenofovir-antigen (test line) and a control line; with an absorbent pad to draw urine across the reaction membrane. Results: We tested 300 urine samples collected from the directly observed therapy study by this LFA and the gold-standard method of LC-MS/MS. The LFA demonstrated 97% specificity (95% CI 93–99%) and 99% sensitivity (94–100%) compared with LC-MS/MS. The LFA accurately classified 98% of patients who took a dose within 24 h as adherent. Conclusion: We describe the development and validation of the first point-of-care assay to measure short-term adherence to HIV prevention and treatment in routine settings. The assay is low-cost, easy-to-perform and measures the breakdown product (tenofovir) of both TDF and tenofovir alafenamide (TAF). This assay has the potential to improve HIV and PrEP outcomes worldwide by triggering differentiated service delivery with further study merited.